Temporal Dynamics of Subjective and Objective Alertness During Exposure to Bright Light in the Afternoon for 5 h - Luo, Xue; Ru, Taotao; Chen, Qingwei; Hsiao, Fan-Chi; Hung, Ching-Sui; Yang, Chien-Ming; Zhou, Guofu (Frontiers in Physiology, 2021)
Light can induce an alertness response in humans. The effects of exposure to bright light versus dim light on the levels of alertness during the day, especially in the afternoon, as reported in the literature, are inconsistent. This study employed a multiple measurement strategy to explore the temporal variations in the effects of exposure to bright light versus regular office light (1200 lx versus 200 lx at eye level, 6500 K) on the alertness of participants for 5 h in the afternoon. Twenty healthy adults (11 females; mean age 23.25 ± 2.3 years) underwent the Karolinska sleepiness scale (KSS), the auditory psychomotor vigilance task (PVT), and the waking electroencephalogram (EEG) test for two levels of light intervention. The results yielded a relatively lower relative delta power and a relatively higher beta power for the 1200 lx condition in comparison to the 200 lx condition. However, the light conditions elicited no statistically significant differences in the KSS scores and performance with respect to the PVT. The results suggested that exposure to bright light for 5 h in the afternoon could enhance physiological arousal while exerting insignificant effects on subjective feelings and performance abilities relating to the alertness of the subjects.